Increasing the resolution of ocean pCO2 maps in the South Eastern Atlantic ocean merging multifractal satellite-derived ocean variables - Hernández-Carrasco, Ismael; Garçon, Véronique; Sudre, Jöel; Garbe, Christoph S.; Yahia, Hussein (IEEE transactions on geoscience and remote sensing, 2018)
A new methodology has been developed in order to improve the description of the spatial and temporal variability of not well-resolved oceanic variables from other well-observed high-resolution oceanic variables. The method is based on the cross-scale inference of information, incorporating the common features of different multifractal high-resolution variables into a coarser one. An exercise of validation of the methodology has been performed based on the outputs of coupled physical-biogeochemical Regional Ocean Modeling System adapted to the eastern boundary upwelling systems at two spatial resolutions. Once the algorithm has been proved to be effective in increasing the spatial resolution of modeled partial pressure of CO2at the surface ocean (pCO2), we have investigated the capability of our methodology when it is applied to remote sensing data, focusing on the improvement of the temporal description. In this regard, we have inferred daily pCO2maps at high resolution (4 km, i.e., 1/24°) fusing monthly pCO2data at low resolution (100 km, i.e., 1°) with the small-scale features contained in daily high-resolution maps of satellite sea surface temperature and Chlorophyll-a. The algorithm has been applied to the South Eastern Atlantic Ocean opening the possibility to obtain an accurate quantification of the CO2fluxes in relevant coastal regions, such as the eastern boundary upwelling systems. Outputs of our algorithm have been compared with in situ measurements, showing that daily maps inferred from monthly products are in average 6 μatm closer to the in situ values than the original coarser monthly maps. Furthermore, values of pCO2have been improved in points close to the coast with respect to the original input data.
Im Titel ist „2“ tiefgestellt
Date of current version October 25 2018
Gesehen am 24.09.2019